Assessing Footwear Factories Under Emergy And Material Flow Accounting Tools After Implementing Cleaner Production Practices - Pacheco, Raquel R. Janot; Almeida, Cecília M.V.B.; Agostinho, Feni; Sevegnani, Fábio; Giannetti, Biagio F.; Liu, Gengyuan (Journal of Environmental Accounting and Management, 2026)
Strategies have been developed in the last decades to improve the sustainability of produced goods, including cleaner production (CP) as an important approach in identifying problems and propose alternatives for improvement under a holistic perspective. Nova Serrana city, located at Minas Gerais state, Brazil, has a footwear cluster considered fundamental for the regional socioeconomic development. However, the production is still based on outdated management techniques that make it economically noncompetitive and cause high load on the natural environment, which claims for studies supporting decisions towards higher sustainability. This work aims to discuss about the results obtained after applying the CP approach in three footwear factories located in Nova Serrana city. Additionally, the factories are assessed under emergy (with an “m”) and material flow accounting tools. Results show that CP was helpful in identifying opportunities for improvement related to better management that is usually easy and cheap to be achieved, including employee training, updating internal control of material storages, reusing scrap materials, and redesigning the procedure of synthetic leather cutting. The indicators obtained from the used environmental accounting tools suggest two approaches for a decision: (i) when pursuing sustainability under a global perspective, footwear factory C should be promoted since it causes lower load on the upstream processes by demanding lower emergy (3.8 E18 sej/yr), abiotic, water and air resources (1.13 E6 kg/yr, 3.66 E7 kg/yr, and 3.82 E5 kg/yr respectively); (ii) when pursuing sustainability by considering socioeconomic short to medium needs, footwear factory B should be promoted since it has higher efficiency in producing footwear (4.03E13 sej/kg for emergy demand, 10.64 kg/kg for abiotic, 319.09 kg/kg for water and 3.96 kg/kg for air). This work contributes with practical basis for the environmental accounting and management of footwear enterprises providing important subsides for decisions.